El caso Birdman - Hayder, Mo (Nuevos tiempos (Madrid, Spain), 2013)
In Greenwich, England, Inspector Jack Caffery investigates the case of a woman with a live bird sewn in her body. The case is the latest in a series of murders of women whose bodies were surgically mutilated.